The effect of endometrial thickness on live birth outcomes in women undergoing hormone-replaced frozen embryo transfer - Rachel A. Martel, B.A; Jennifer K. Blakemore, M.D., M.Sc; James A. Grifo, M.D., Ph.D (Elsevier, 2021)
Objective: To determine the impact of endometrial thickness on live birth outcomes and obstetric complication rate after hormone-replaced frozen embryo transfer. Design: Retrospective cohort study. Setting: Large, urban, academic fertility center. Patient(s): All patients with a singleton live birth after single euploid embryo transfer (by array comparative genomic hybridization or next-generation sequencing) in a hormone-replaced frozen embryo transfer cycle between January 2017 and December 2018 were reviewed. Intervention(s): None. Main Outcome measure(s): The primary outcomes were birth weight and obstetric complication rate. Result(s): A total of 492 patients were included. The median endometrial thickness was 8.60 mm (range, 6.0-20.0). The median gestational age at live birth was 39.4 weeks with a median birth weight of 3,345.2 g. Endometrial thickness was significantly correlated with birth weight. When patients were dichotomized into groups (those with an endometrial thickness of <7 mm and those with an endometrial thickness of >7 mm), neonates born from endometria with a thickness of <7 mm were born earlier (37.3 vs. 39.4 weeks and born with lower birth weights (2,749.9 vs. 3,345.2 g). It should be noted that only seven patients had an endometrium measuring <7 mm. Moreover, 7.1% (n = 35) of patients had an obstetric complication. Endometrial thickness was not significantly associated with obstetric complications, even with adjustments for age and medical history. Conclusion(s): Endometrial thickness may be a valuable predictor of placental health and birth weight. Further study is required to examine the relationship with individual obstetric complications, as our study may not have been powered to observe differences in obstetric complication rate, as well as the relationship between endometrial thickness and outcomes in natural frozen embryo transfer cycles.